THE USE OF A MIXTURE OF SOMATIC AND CULTURE FILTRATE ANTIGENS IN THE EVALUATION OF THE IMMUNE-RESPONSE TO PARACOCCIDIOIDES-BRASILIENSIS - Dasilva, MIC; Decarvalho, I. M.; Franco, T. N.; Cunha, M. A.; Chamma, L. G.; Fogaca, J.; Fecchio, Denise [UNESP]; Franco, M. (Blackwell Science, 1991)
Three Paracoccidioides brasiliensis antigens, namely a culture filtrate preparation, a somatic antigen and a mixture of equal parts of the two, were tested by two serological techniques against sera from patients with paracoccidioidomycosis, and in an in vivo delayed hypersensitivity model in mice. The antigen mixture was more sensitive than the two individual antigens for the evaluation of the humoral and cellular immune response to P. brasiliensis, both in man and in experimental animals.